Fluorescent imaging and bio-cellular uptake assessment of gold-near infrared dye conjugated cockle shell calcium carbonate nanoparticles - Kiranda, H.K.; Mahmud, R.B.; Mahmood, S.K.; Zakaria, Z.A. (University of Mosul - College of Veterinary Medicine, 2024)
In recent years, fluorescent imaging has emerged as an active area of interest in medical imaging. Fluorescent imaging plays a critical role in molecular imaging. Evidence suggests its use in providing a detailed structural outlook and genetic and cellular operatives of the body procedures on a molecular plane. Imaging agents are identified to be related to risks such as not biologically disintegration and great poisonousness. Researchers have shown a keen attentiveness to the growth of targeted multifunctional agents in oncology and near-infrared (NIR) fluorescence imaging. This study assessed fluorescent imaging and bio-cellular acceptance of the gold (NIR) conjugated cockle shell-derived calcium carbonate nanoparticles Au-CsCaCO3NPs. The synthesized Au-CsCaCO3NPs were characterized by Transmission electron microscopy (TEM) for size and morphology, Zeta potential, and UV-Vis spectrophotometer. Biocompatibility of Au-CsCaCO3NPs in cultured human breast carcinoma cells MCF-7 and mouse embryonic fibroblast cells NIH3T3 was evaluated using bioassays like Lactate Dehydrogenase LDH and Reactive Oxygen Species ROS for toxic examination. Cellular morphology and uptake were studied by fluorescence and confocal microscopy. The outcomes proved that MCF-7 treated Au-CsCaCO3NP cells observed more cell deaths than NIH3T3 treated Au-CsCaCO3NP cells. Additionally, the cells were capable of assuming nanoparticles within their cellular compartments. In conclusion, gold-near infrared dye conjugated cockle shell calcium carbonate nanoparticles Au-CsCaCO3NPs were easily synthesized, biocompatible, and environmentally friendly. It is safe to state that the Au-CsCaCO3NPs could be used for imaging and could present opportunities for progressing cancer imaging.